Mould Filling In Electronic Packaging - Chu, Wee Liang (Universiti Sains Malaysia, 2004)
This final year project focuses on the study of flow in encapsulation processes in electronic packaging industry. The present work adopted a 2D Hele-Shaw model to study the flow of Newtonian and Non-Newtonian (power law) fluids into cavities at various distances from transfer ram in the transfer molding process. The velocity field obtained from both Hele-Shaw and generalized porous medium approaches is used in pseudo-concentration algorithm for front tracking with an artificial diffusion term added to allow partial slip at the fluid-wall interface and to damp numerical oscillation to a minimum level. Finite Element Method is employed in all the analyses to reduce the governing partial differential equations to algebraic equations. Parametric studies had been carried out to study how the dimension and parameter of the mold tools affects the flow filling’s behavior. From parametric study we can show that by altering the dimensions of mold tools, thus introducing different hydraulic resistances at various in-line cavities in appropriate proportions, will lead to balance filling in transfer molding.